From local bacterial communities to energy: application of microbial fuel cells in laboratory experimentation - Esteban Pazmiño-Arias; Abigail Montero-Calderon; Mariela Perez-Cárdenas; Marco Esteban Gudiño Gomezjurado (Journal of Microbiology & Biology Education)
ABSTRACT It is well known that bacterial communities are an essential component to maintain the balance of terrestrial ecosystems due to the functions and services performed by microorganisms in the environment. The research seeking on alternative energy sources has shown that bacterial communities can bioconvert the chemical energy of an organic substrate into electrical energy, within devices known as microbial fuel cells. For this reason, this class project allows students of Biotechnology, Environmental Science, and Microbiology to apply the appropriate methodology to develop a class project throughout an environmental bacterial community capable of generating electrical energy.